(untitled) (International Journal of Biology and Chemistry, 2025)
Bacterial, fungal, and viral contaminations pose a pervasive challenge to in vitro propagation of berry crops, presenting significant economic hurdles for the preservation of plant genetic resources and the commercialization of micropropagation. This study aimed to diagnose endophytic and viral contamination in commercial blackberry cultivars and while developing an in vitro method to eliminate bacterial contamination from the Chaсanska Bestrna variety. The Plant Preservative Mixture™ (PPM™) was utilized as a broad-spectrum bactericidal agent within the blackberry in vitro tissue culture. Contaminated shoots were cultured on Murashige and Skoog medium supplemented with 0.2% v/v PPM™, maintained over a 12-week period through three subcultures, before being transferred to medium devoid of PPM™ for an additional 12 weeks. The results were evaluated after 12 and 32 weeks of culture on medium without PPM™. This study demonstrated that PPM™ is an effective control agent and can be successfully used to manage the growth of endophytic contamination. For the Chaсanska Bestrna blackberry variety, 100% aseptic shoots were obtained in vitro without any negative effects on the shoot growth. However, the results indicate the opportunity for further testing of PPM™ on other blackberry varieties experiencing bacterial contamination, as it is possible that the contamination in this study was superficial and the selected concentration of the bactericide proved to be successful. To obtain virus-free planting stocks, in vitro rooted shoots were transferred to a soil substrate consisting of peat (40%), black soil (50%), and perlite (10%), and then adapted in a greenhouse at 20-23°С. The survival rate of blackberry varieties in greenhouse conditions was 93-99%. Keywords: blackberry; tissue culture; in vitro contamination; micropropagation; broad-spectrum biocide